Addressing Prison Education and the Obstacles in Ensuring the Right to Education in Indonesian Juvenile Correctional Facilities - Prayitno, Kuat Puji; Oktobrian, Dwiki; Barkhuizen, Jaco (University of Jember, 2023)
Reintegrating juvenile offenders into society with a positive reception is a primary objective of education, aimed at breaking the cycle of incarceration that results in recidivism. This article aims to delineate the prison education policies within Indonesian juvenile correctional facilities (LPKA), focusing on regulatory frameworks and their practical implementation. It focuses on the issue of the LPKA's capability in Indonesia to ensure access to education, which is a fundamental right of juvenile inmates, and on whether its benefits can be felt and realized. Data collection methods encompassed interviews, regulatory assessments, institutional report evaluations, and literature reviews. Findings indicate that, despite a 270% decrease in juvenile inmate numbers from 2018 to 2022, only 68% of this population was granted educational access. Contributing factors include specific regulatory constraints on educational access and a lack of innovative collaborations, even with the reduced workload in LPKA. The study advocates for the initiation of formal educational institutions within LPKA, minimizing reliance on the Ministry of Education and allowing for curriculum adaptation to prevailing conditions. Keywords: Prison Education, Right to Education, Juvenile Correctional Facilities, Juvenile Inmates, Social Rehabilitation